Emissive Metallacycle‐Crosslinked Supramolecular Networks with Tunable Crosslinking Densities for Bacterial Imaging and Killing. (11th June 2020) - Jeyakkumar, Ponmani; Liang, Yongping; Guo, Mengying; Lu, Shuai; Xu, Donghua; Li, Xiaopeng; Guo, Baolin; He, Gang; Chu, Dake; Zhang, Mingming
Abstract: The chemical structures and topologies of the crosslinks in supramolecular networks play a crucial role in their properties and functions. Herein, the preparation of a type of poly(N‐isopropylacrylamide) (PNIPAAM)‐based supramolecular networks crosslinked by emissive hexagonal metallacycles is presented. The topological connections in these networks greatly affect their properties, as evidenced by their differences in absorption, emission, lower critical solution temperature, and modulus along with the variation of crosslinking densities. The integration of PNIPAAM and metallacycles in the networks benefits them improved bioavailability, making them serve as reagents for bacterial imaging and killing. This study provides a strategy to prepare cavity‐crosslinked polymer networks for antibacterial applications. Abstract : View to a kill : Emissive metallacycle‐crosslinked supramolecular networks with hexagonal metallacycles as their crosslinks were developed. These networks were employed for bacterial imaging and killing based on the properties of the introduced metallacycles.